From Tradition to Modernity: Economic Growth in a Small World - Ines Lindner; Holger Strulik (Leibniz Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2011)
This paper introduces the Small World model (Watts and Strogatz, Nature, 1998) into the theory of economic growth and investigates how increasing economic integration affects firm size and effciency, norm enforcement, and aggregate economic performance. When economic integration is low and local connectivity is high, informal norms control entrepreneurial behavior and more integration mainly improves search for effcient investment opportunities. At a higher level of economic integration neighborhood enforcement deteriorates and formal institutions are needed to keep entrepreneurs in check. A gradual take-off to perpetual growth is explained by a feedback effect from investment to the formation of long-distance links and the diffusion of knowledge. If formal institutions are weak, however, the economy does not take off but stagnates at an intermediate income level. Structurally, the equilibrium of stagnation differs from balanced growth by the presence of relatively many small firms of low productivity.
Keywords: O10; O40; L10; L14; Z13; 330; modernization; economic integration; firm size; norms; networks; knowledge spillovers; growth